Development and Validation of a Syndrome Definition for Suspected Nonfatal Unintentional/Undetermined Intent Stimulant-Involved Overdoses. (November 2022) - Pickens, Cassandra M.; Scholl, Lawrence; Liu, Stephen; Smith, Herschel; Snodgrass, Stephanie
Objectives: To monitor stimulant-involved overdose (SOD) trends, the Centers for Disease Control and Prevention (CDC) developed and evaluated the validity of a syndromic surveillance definition for suspected nonfatal, unintentional/undetermined intent stimulant-involved overdose (UUSOD). Methods: We analyzed all emergency department (ED) visits in CDC's surveillance system that met the UUSOD syndrome definition (January 2018–December 2019). We classified visits as true positive, possible, or not UUSODs after reviewing diagnosis codes and chief complaints. We first assessed whether visits were acute SODs, subsequently classifying acute SODs by intent. The percentage of true-positive UUSODs did not include intentional or possibly intentional visits. We considered all visits with UUSOD diagnosis codes to be acute SODs and reviewed them for intent. We manually reviewed and double-coded a 10% random sample of visits without UUSOD diagnosis codes using decision rules based on signs and symptoms. The overall percentage of true-positive UUSODs was a weighted average of the percentage of true-positive UUSODs based on diagnosis codes and the percentage of true-positive UUSODs determined by manually reviewing visits without codes. Results: During 2018-2019, 40 045 ED visits met the syndrome definition for UUSOD. Approximately half (n = 18 793; 46.9%) of 40 045 visits had UUSOD diagnosis codes, indicating acute SOD; of these, 98.6% (n = 18 534) were true-positive UUSODs. Of 2125 manually reviewed visits without UUSOD diagnosis codes, 32.6% (n = 693) were true-positive UUSODs, 54.2% (n = 1151) were possible UUSODs, and 13.2% (n = 281) were not UUSODs. Overall, 63.6% of visits were true-positive UUSODs, 29.3% were possible UUSODs, and 7.1% were not UUSODs. Practice Implications: CDC's UUSOD definition may assist in surveillance efforts with further refinement to capture data on SOD clusters and trends.